(untitled) (Research, Society and Development, 2022)
In this work, a proposal will be presented for a study of recovery of a degraded area located in the city of Patos-PB, affected by the indiscriminate use in agricultural activity, as well as in the extraction of natural resources, in which, the physical, chemical and biological characteristics of the areas appear altered. The degraded areas are characterized by the removal of abundant vegetation and riparian forests, which is visible in the study area presented throughout the entire work. The use of georeferenced images and digital photographs, as well as visits to the area, were used in this study. Measures and techniques will be imposed in the area, aiming not only at the recovery, as well as at the possibility of reusing the area. So that at the end of the entire recovery process, everyone benefits.